2017
DOI: 10.1007/s13201-017-0553-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical characteristics and assessment of water quality in the Al-Saad Lake, Abha Saudi Arabia

Abstract: Hydrogeochemical characteristics and assessment of water quality investigations have been carried out at Abha, located in Saudi Arabia, where Al-Saad Lake represents a rare example of natural endorheic lake. The ecosystem within and around the Al-Saad Lake including catchment area is of great social, cultural, aesthetic, environmental and economic values to Abha. The result obtained in this investigation inferred that the cations in water i.e. sodium and iron are within the permissible limits but magnesium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Various studies such as National Research Council and Mono Basin Ecosystem Study Committee (1987), Council and Bennett (1993), Habersack and Nachtnebel (1995), Tenzer et al (1997), Hernandez and Ernest (1999), Schoonover et al (2005), Salvia-Castellví et al (2005, Salomons and Stigliani eds (2012), Mallick (2017), Thakur et al (2018), Denizman (2018), Jasrotia et al (2018), and Roy et al (2018) have shown that sediment-water interactions and the human activities such as agrarian and forestry practices, as well as the release of domestic wastewaters into the water bodies, are statistically related as have been analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies such as National Research Council and Mono Basin Ecosystem Study Committee (1987), Council and Bennett (1993), Habersack and Nachtnebel (1995), Tenzer et al (1997), Hernandez and Ernest (1999), Schoonover et al (2005), Salvia-Castellví et al (2005, Salomons and Stigliani eds (2012), Mallick (2017), Thakur et al (2018), Denizman (2018), Jasrotia et al (2018), and Roy et al (2018) have shown that sediment-water interactions and the human activities such as agrarian and forestry practices, as well as the release of domestic wastewaters into the water bodies, are statistically related as have been analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the plot of HCO 3 versus Ca (Fig. 8) indicates the ionic association between them (Saber et al 2013;Mallick 2017). …”
Section: \002mentioning
confidence: 99%
“…On the other hand, the plots of HCO 3 versus SO 4 and SO 4 versus Cl (Fig. 8) show that the pollutants are inputs from the soil surface and their origin is the same: from fertilizers and from animal and human wastes (Saber et al 2013;Mallick 2017;Unnisa S and Zainab Bi 2017). According to WHO standards, the admissible levels of Cu, Zn, Al, Cd, and Fe in potable water are 2, 3, 0.2, 0.003, and 0.2 mg/l, respectively.…”
Section: \002mentioning
confidence: 99%
See 1 more Smart Citation
“…The surface water quality depends not only on natural processes, i.e. precipitation inputs, erosion, and weathering of crustal materials, but also on anthropogenic influences (Mallick, 2017). Here domestic and agricultural consumption generally predominate over other water uses (Davraz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%